Cytotoxicity - Definition, Identification, and Cytotoxic Compounds 2019
DOI: 10.5772/intechopen.87177
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effect and Mechanisms from Some Plant-Derived Compounds in Breast Cancer

Abstract: Breast cancer (BrC) is a major health problem in women all around the world. A growing knowledge about these alterations and their associated molecular signaling pathways offers opportunities for therapeutic strategies; chemotherapy is one of the most utilized treatments; however, because of the adverse side effects and multidrug resistance that patients may present, there has been great advancement in search of new alternatives as the use of plant-derived natural compounds. This review describes information o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 98 publications
(134 reference statements)
0
6
0
Order By: Relevance
“…Plant derived compounds have different modes of action; however, most of them induce apoptosis without cytotoxic effect on normal cells 54 . Recently it was reported that in phenols, the number of substitutes in the OH-ring, increases its anti-proliferative and cytotoxic activities 55 . Similarly, terpenes, terpenoids, alkaloids and flavonoids induce cytotoxicity of breast cancer cells by activating the intrinsic pathway resulting in apoptosis 55 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant derived compounds have different modes of action; however, most of them induce apoptosis without cytotoxic effect on normal cells 54 . Recently it was reported that in phenols, the number of substitutes in the OH-ring, increases its anti-proliferative and cytotoxic activities 55 . Similarly, terpenes, terpenoids, alkaloids and flavonoids induce cytotoxicity of breast cancer cells by activating the intrinsic pathway resulting in apoptosis 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently it was reported that in phenols, the number of substitutes in the OH-ring, increases its anti-proliferative and cytotoxic activities 55 . Similarly, terpenes, terpenoids, alkaloids and flavonoids induce cytotoxicity of breast cancer cells by activating the intrinsic pathway resulting in apoptosis 55 . Significant cytotoxic and antitumor activity of methanol and aqueous extracts of L. nobilis leaves towards a number of cancer cell lines, like NCI-H460-lung cancer cells, cervical carcinoma, HCT15-colon carcinoma, breast adenocarcinoma and HepG2 -hepatocellular carcinoma have been reported earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Over 200 novel chemical compounds have been licensed for use in the battle against cancer in the last 50 years, with about 50% being molecules of unaltered natural products [ 21 ]. Small organic molecules of secondary metabolites have played an essential role in inhibiting proliferation-induced apoptosis or other modifiable mechanisms [ 22 , 23 , 24 ].…”
Section: The Activity Of Amg In Breast Cancermentioning
confidence: 99%
“…The mechanism of action of plant-derived bioactive compounds involves inhibition of various cellular activities, and the potency of plant-derived chemical agents is dependent on the dosage [ 30 ]. Figure 2 illustrates various steps involved in tumor development and its fate.…”
Section: Mechanisms Of Plant-derived Agents Induced Cell Deathmentioning
confidence: 99%